Effects of 15-Day Head-Down Bed Rest on Emotional Time Perception - Qian, Yiming; Jiang, Shan; Jing, Xiaolu; Shi, Yusheng; Qin, Haibo; Xin, Bingmu; Chi, Lizhong; Wu, Bin (Frontiers in Psychology, 2021)
Accurate time perception is clearly essential for the successful implementation of space missions. To elucidate the effect of microgravity on time perception, we used three emotional picture stimuli: neutral, threatening, and disgusting, in combination with a temporal bisection task to measure 16 male participants' time perception in 15 days of -6° head-down bed rest, which is a reliable simulation model for most physiological effects of spaceflight. We found that: (1) participants showed temporal overestimation of the threatening stimuli in the middle phase (day 8), suggesting that when participants' behavioural simulations were consistent with the action implications of the emotional stimuli, they could still elicit an overestimation of time even if the subjective arousal of the emotional stimuli was not high. (2) Participants' temporal sensitivity tends to get worse in the bed rest phase (day 8 and day 15) and better in the post-bed rest phase, especially for neutral and threatening stimuli, suggesting that multiple presentations of short-term emotional stimuli may also lead to a lack of affective effects. This reduced the pacemaker rate and affected temporal perceptual sensitivity. Also, this may be related to changes in physiological factors in participants in the bed rest state, such as reduced vagal excitability. These results provide new evidence to support the theory of embodied cognition in the context of time perception in head-down bed rest and suggest important perspectives for future perception science research in special environments such as microgravity.